Teorema de Pitágoras: interdisciplinaridade e suas aplicações - Santos, Antonio Wiliame Nogueira dos (2020)
It is a research that presents knowledge of Mathematics in High School about interdisciplinarity and its applications, which provides a teaching-learning based on the student's daily life. One of the biggest problems present in the educational context is the interdisciplinarity in the learning and teaching of Mathematics. In general, currently, there are certain difficulties in establishing relations between the contents with the in- tegration and the applications of Mathematics with the other areas present in the curricula. The student, only through “reading the world view” around him, with the work of several disciplines together, will have a more integrated and global notion, better developing the capacity for quality teaching and learning. Therefore, the research has a bibliographic nature, with a qualitative character, with searches in electronic journals such as Google Scholar, Scientific Electronic and Library Online (SciELO).